Argumentative Bullshit - Gascón, José Ángel (Informal Logic, 2021)
Harry Frankfurt characterised bullshit as assertions that are made without a concern for truth. Assertions, however, are not the only type of speech act that can be bullshit. Here, I propose the concept of argumentative bullshit and show how a speech acts account of bullshit assertions can be generalised to bullshit arguments. Argumentative bullshit, on this account, would be the production of an argument without a concern for the supporting relation between reasons and claim.